Upaya Peningkatan Kesehatan Anak Dengan Penyuluhan Kesehatan Tentang Imunisasi pada Balita di Desa Gebang RW XV Kelurahan Banjarsari Surakarta - Hutari Puji Astuti; Christiani Bumi Pangesti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Immunization is an efficient way to prevent disease and is a priority in preventive medicine. Until now there are seven infectious diseases in children that can cause death and disability, although some children can survive and become immune. The purpose of this community service is to increase the knowledge of the women of Gebang Village, RW XV, Banjarsari Surakarta, and these mothers can understand about immunization in toddlers. The method used in this activity is through lectures, discussions and questions and answers, with the target audience being women from Gebang Village, RW XV, Banjarsari Village, Surakarta. The conclusion of immunization counseling activities for children under five is an increase in the knowledge of mothers from Gebang Village RW VX about immunization for children under five. Knowledge of the mothers of Gebang Village RW VX includes understanding, objectives, requirements for immunization and various types of immunization for children under five. This is evidenced by the average post-test score on immunization for children under five with an increase of 90%. The increased knowledge of the mothers of Gebang Village, RW XV, Banjarsari Surakarta, is expected to increase immunization coverage for children under five in the area. Suggestions from this activity are expected that health workers, especially midwives, can improve midwifery care for children under five so that they can provide optimal service to every child under five so that the health status of children under five will increase.